THE EFFECTS OF MACHINES USED IN APPAREL COMPANIES TO THE PROFITABILITY - KONFEKSİYON İŞLETMELERİNDEKİ MAKİNELERİN ÜNAL; M. Çetin ERDOĞAN; Ziynet Öndoğan (Pamukkale University Journal of Engineering Sciences, 2005)
There are strong competition conditions at the market of ready made garment products which has an important part of world trade. In this sector, the technology development and research facilities have an important place because of the quality and technology are at the priority position. In our country, Turkey, lots of manufacturers tend to added valued and profitable products instead of usual, low priced and low added valued products. In this situation, new technologies must be used. But the usage of this kind of tecnologies could not be suitable for every company. The sewing automat is a kind of system group that can do any kind of sewing operation by itself. These kinds of complex machines need less number but more skilfull of workers. Decreasing of order quantities, fastly changing product and production types are given necessary to the workers for suiting these changes. In this paper, increasing of production quantity without changing quality was researched. For this purpose, ideal production method was proposed with the comparision of classical sewing machines and sewing automats for the point of production methods view.